Traditional Ecological Knowledge and Farm Household Resilience to Natural Hazards - Arini Wahyu Utami; Nadila Puspa Arum Widjanarko; Didik Indradewa; Aura Dhamira; Mutiarra Ridyo Arum; Fathi Alfinur Rizqi; Nurul Amri Komarudin; Din Prabaningtyas (Caraka Tani: Journal of Sustainable Agriculture, 2024)
This study portrays the roles of Traditional Ecological Knowledge (TEK) in the mitigation of natural hazards. Menoreh Hill in Kulon Progo experienced more than 200 landslides in 2022 and its communities implemented TEK to mitigate them. Hence, this research quantitatively analyzes the role of agriculture-related TEK, especially those applied in hilly areas, to support household resilience to natural hazards. Authors surveyed 106 farm households and interviewed eight key informants in Banjararum and Sidoharjo Villages, Kalibawang and Samigaluh Sub-districts, Kulon Progo Regency, D.I. Yogyakarta. The data were then analyzed using descriptive statistics and binary logistic regression. The descriptive statistics showed that farmers in both villages are highest in practicing alley cropping and integrated farming, while also applying mixed cropping, multiple cropping and locally based planting schedule (pranata mangsa). From binary logistic regression, authors found that TEK practices of multiple cropping, alley cropping and pranata mangsa support farm household resilience to natural hazards, especially landslides. The TEK practices serve as sources of buffer and adaptation capacity in the development of farm household resilience. Interestingly, mixed cropping and membership in farmer groups tend to weaken resilience, as mixed cropping often complicates the recovery efforts in the farmlands, and farmers’ groups are not conditioned to act promptly during hazards or disasters. While TEK has been proven to take roles in the mitigation and adaptation to natural hazards, there is a need to integrate scientific knowledge to improve its optimum benefits.